Isolation and Characterization of Bacteria from Earthworms’ Intestines - Shaarani, Shalyda Md; Jia, Yap Shu; Arshad, Zatul Iffah Mohd; Man, Rohaida Che; Mudalip, Siti Kholijah Abdul; Sulaiman, Siti Zubaidah (International Journal of Engineering and Technology, 2018)
Vermicomposting; breaking down of organic material by earthworms that feed on wastes and converts them to soil-like mass and liquid, is an alternative to reduce waste into the environment. Nitrogen fixing and Phosphorus solubilizing bacteria in the earthworms’ intestines are important in promoting plant growth by increasing the Nitrogen (N) and Phosphorus (P) uptake when used as biofertilizers. The objectives of this study are to isolate, identify and characterize N-fixing and P-solubilizing bacteria from the earthworms’ intestines. The preparation of vermibeds included the introduction of leachate taken from Sungai Ikan Landfill, Kuala Terengganu. Standard serial dilution procedure was performed to isolate the microorganisms. Next, identification and characterization of bacteria were conducted via gram staining and bacteria morphological characteristic studies. Qualitative screening of N-fixing bacteria was performed by Hach Method 8039 while screening of P-solubilizing bacteria used Pikovskaya’s Agar containing insoluble tri-calcium phosphate (TCP). Six isolates, (A1, A2, B1, B2, C1 and D1) were successfully isolated. However, only single colony of A1, A2, B1 and B2 were obtained. All were gram negative and bacilli except for A1. A2 showed the highest nitrogen fixing and phosphate solubilizing activity though with the nitrate content (148.6 mg/L) and high phosphate solubilization efficiency (10.6).